Identification of selective cyclin-dependent kinase 2 inhibitor from the library of pyrrolone-fused benzosuberene compounds: an in silico exploration. Issue 17 (22nd November 2022) - Singh, Rahul; Bhardwaj, Vijay Kumar; Sharma, Jatin; Das, Pralay; Purohit, Rituraj
Abstract: The over-expression of cyclin-dependent kinase 2 is related to multiple cancers, which has led them to be a widely researched topic for nearly two decades. The prime focus of the present research is to design new potent and specific inhibitors against CDK2 to suppress cancer cell proliferation. In this study, we have chosen Flavopiridol, SU9516, and CVT-313 as standard inhibitors to compare with in-house synthesized pyrrolone-fused benzosuberene (PBS) compounds. We scrutinized Ligand2 as a selective inhibitor of CDK2 without off-target binding (CDK1 and CDK9) based on ligand efficiency and binding affinity. Interpretation of dynamic simulations and binding free energy studies unveiled that Ligand2 has a stable and equivalent free energy to standard inhibitors. These outcomes led towards positioning a potential natural molecule as selective inhibitor for CDK2 with low side effects. GRAPHICAL ABSTRACT: UF0001 Communicated by Ramaswamy H. Sarma